Ginkgo biloba extract prevents against apoptosis induced by high glucose in human lens epithelial cells - Wu Zheng-mei; Yin Xiao-xing; Ji Lei; Gao Yuan-yuan; Pan Ying-mei; Lu Qian; Wang Jian-yun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the protective effects of Ginkgo biloba extract (GBE) on high glucose-induced apoptosis of human lens epithelial cells (HLEC) and the possible molecular mechanisms. Methods: The cultured HLEC were allotted into 6 groups: normal group, high glucose group, low-, moderate-, and highdose GBE group, and the bendazac lysine group. Cell viability, cell apoptosis, the activities of cell antioxidases, aldose reductase, caspase-3, the levels of cell antioxidants, and the expressions of Bcl-2 and Bax were assessed by different methods. Results: After being incubated with high glucose for 24 h, HLEC underwent apoptosis and exhibited significant oxidative stress. In the presence of GBE at different doses, the rate of HLEC apoptosis was lower and the oxidative stress state was significantly ameliorated. The increased ratio of Bax to Bcl-2 was significantly reduced and the activation of caspase-3 was suppressed by GBE in a dose-dependent manner. Conclusion: GBE prevents HLEC from high glucose-induced apoptosis through inhibiting oxidative stress, reducing the ratio of Bax to Bcl-2, and decreasing the activity of caspase-3. Therefore, GBE has a potential protective effect against diabetic cataract formation.